Biodiversity of the metazoan parasites of Prochilodus lineatus (Valenciennes, 1837) (Characiformes: Prochilodontidae) in anthropized environments from the Batalha River, Sao Paulo State, Brazil - Rosa Leite, Lucas Aparecido [UNESP]; Pelegrini, Larissa Sbeghen [UNESP]; Agostinho, Beatriz Narciso; Azevedo, Rodney Kozlowiski de; Abdallah, Vanessa Doro (Revista Biota Neotropica, 2018)
Biodiversity of fish parasites is a field of significant growth worldwide, whether due to the advancement of fish farms or the important role of these organisms as indicators of environment quality and ecosystem health, making them useful tools in the conservation and maintenance of the biodiversity as a whole. The objectives of this study were to evaluate the structure and composition of the parasitic fauna of Prochilodus lineatus collected from two structurally distinct stretches of the Batalha River. Fifty specimens of P. lineatus were collected between June 2015 and June 2016. Of these 50 hosts, 875 parasite specimens were collected, divided into 30 species, belonging to seven groups: Myxozoa, Monogenea, Digenea, Acanthocephala, Nematoda, Copepoda and Hirudinea. In addition to new records of known parasites of P. lineatus for this locality, 13 species were newly recorded parasitizing this fish, including a new monogenean species (Tereancistrum sp. n.), with Monogenea being the most representative class in the study. The findings of this study expands the known geographic distribution of these parasite species and helps to increase the knowledge of the biodiversity of these organisms in different hosts and environments. In general, the structure and composition of the P. lineatus parasitic fauna did not seem to be influenced by the structural characteristics of the two stretches studied, due to the migratory habits of the host.
Keywords: Parasitic diversity; Curimbata; Lentic ecosystems; Lotic ecosystems; Tiete-Batalha River basin